Effects of Aerobic Exercise on Cognitive Function and Affected Arm Function in Individuals with Ischemic Stroke - Rima Solianik; Justina Armanavičiūtė (Lithuanian Sports University, 2020)
Background. Aerobic exercise has been successfully applied for cognitive and motor function improvement; however, its effects on the affected arm function in individuals with stroke remains equivocal. Research aim. The aim of this study was to determine the effects of aerobic exercise on cognitive function and affected arm function in individuals with ischemic stroke. Methods. The study included 16 subjects with ischemic stroke. They were randomly assigned to control (30 min of usual physiotherapy) and experimental (30 min of usual physiotherapy plus 20 min of aerobic exercise) groups. The interventions were performed five times a week, for 8 weeks. Cognitive performance and the affected arm function were evaluated before and after interventions. Results. In the experimental group, improvement (p < 0.05) in the affected arm function and attention were observed. Both interventions significantly improved (p < 0.05) cognitive flexibility; however, greater improvement (p < 0.05) was observed after experimental intervention compared with control intervention. No differences in intervention effects on working memory were observed. Conclusions. Aerobic exercise, which is performed immediately after physiotherapy, improves recovery of impaired arm function, attention, and cognitive flexibility in individuals with ischemic stroke. Keywords: endurance exercises, motor function, aerobic exercise, cognitive flexibility.